Effects of Hemin on neuroglobin expression after cardiopulmonary resuscitation in rats - He, Ai-wen (Second Affiliated Hospital of Zhejiang University School of Medicine, 2011)
BACKGROUND: Despite a large amount of resuscitation research, the survival rate after cardiac arrest remains low, and brain injury is the key issue. Neuroglobin (NGB) is an oxygen-binding heme protein found in the brain with a protection role against ischemic-hypoxic brain injury. Hemin is an effective activator of neuroglobin. This study was undertaken to assess the effect of hemin on expression of neuroglobin (NGB) in the cerebral cortex, neuro-deficit score (NDS) and pathological changes after cardiopulmonary resuscitation (CPR) in rats. METHODS: A total of 120 male Sprague-Dawley (SD) rats were randomly divided into a control group (A), a CPR group (B) and a Hemin group (C). The animal model of cardiac arrest (CA) induced by asphyxia and CPR was established. NGB expression in the cerebral cortex with immunohistochemistry, NDS and pathological changes in the cerebral cortex were examined at 3, 6, 12, 24 hours after recovery of spontaneous circulation (ROSC) in each group. Experimental data were treated as one-factor analysis of variance and the Tukey test. RESULTS: In comparison with group A, NGB expression was increased significantly at 12 and 24 hours after ROSC (P<0.05 or P<0.01), NDS was decreased significantly at each time point after ROSC (P<0.01), and pathological changes were severe at each time point after ROSC in group B. In comparison with group A, NGB expression was increased significantly at 6, 12, 24 hours after ROSC (P<0.05 or P<0.01), NDS was decreased significantly at 3, 6, 12 hours after ROSC (P<0.01) in group C. In comparison with group B, NGB expression was increased significantly at 12 and 24 hours after ROSC, NDS was increased significantly at 12 and 24 hours after ROSC, and pathological changes were milder in group C. CONCLUSION: There were increased NGB expression in the cerebral cortex, decreased NDS, and severe pathological changes after CPR in rats. Hemin treatment up-regulated expression of NGB, improved NDS, mitigated pathological changes, and alleviated cerebral injury after CPR.